Peran Laminar Air Flow Cabinet Dalam Uji Mikroorganisme Bagi Mahasiswa Tugas Akhir Di Laboratorium Biokimia - Harjanto, Sri; Raharjo, R (Jurnal Pengelolaan Laboratorium Pendidikan, 2019)
Work safety and safety in the laboratory environment is needed. Based on the method of classification of the number of appliances usage. In this case from the observation / survey that the number of users of Laminar air flow in biochemical laboratories for 1 year (2017) this shows a very significant number, especially in certain months such as October - November reached the number 27, 31 users, the overall number of users enough many. This means showing that the instrument is needed for its existence.Also from the type of activities undertaken by students of Final Project so far by using these instruments can be served well means the tool is able to help solve the problems of students who are completing the research. Keywords: Microorganism, Laminar Air Flow, Safety